Faculty Advising: Teaching, Research, or Service? - Wendy Troxel; Jennifer Joslin (Academic Chairpersons Conference Proceedings, 2019)
Mentoring and advising from faculty members play a major role in students’ understanding of higher education, the curriculum, and ownership of meeting their academic goals and career aspirations. This interactive session addresses the incentives (or lack of incentives) for faculty to see academic advising as a fundamental and rewarding element of their work in higher education.
Keywords: Faculty Advising; Mentoring; Professional Development; Rewards Structures